Efficient, direct synthesis of dimethyl carbonate from CO2 using a solid, calcined zirconium phenylphosphonate phosphite catalyst - Unnikrishnan, Pulikkeel; Varhadi, Poonam; Srinivas, Darbha (RSC Advances, 2013)
Direct synthesis of dimethyl carbonate (DMC) from CO2 and methanol with 100 mol% selectivity using a solid, reusable, hydrophobic, calcined zirconium phenylphosphonate phosphite catalyst is reported for the first time. DMC yield as high as 26 mmol g(-1) catalyst correlated with the concentration of acid and base sites is obtained.

Effects of method of preparation on catalytic activity of Co-Zn double-metal cyanide catalysts for copolymerization of CO2 and epoxide - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2014)
Co-Zn double-metal cyanide (DMC) complexes are well-known catalysts for ring-opening polymerization of epoxides and co-polymerization of CO2 and epoxides. This work provides an insight on structure-activity relationship of DMC for poly(cyclohexene carbonate) synthesis. Seven samples of DMC were prepared by different methods and mode of reagent addition. Highly active catalyst could be synthesized even without using a co-complexing agent. CO2 adsorption studies revealed that higher the guest-host interaction higher would be the catalytic activity. High density and strength of Lewis acid sites, moderate crystallinity, low crystal symmetry (rhombohedral/monoclinic), Cl- ions and coordinated tert.-butanol (complexing agent) control the catalytic activity for polycarbonates. Chloride in the structure avoided induction period by increasing acidity of the catalyst and thereby, improving the guest-host interactions. Polycarbonates with CO2 incorporation as high as 86 mol%, average molecular weight of 20900 and polydispersity index of 1.8 were prepared at complete conversion of cyclohexene oxide. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; CO2 utilization; Copolymerization of CO2 and cyclohexene oxide; Double-metal cyanide; Polycarbonate; Structure-activity relationship

Effect of alkali and alkaline earth metal ions on benzyl alcohol oxidation activity of titanate nanotube-supported Au catalysts - Nepak, Devadutta; Srinivas, Darbha (RSC Advances, 2015)
Sodium titanate nanotubes (NaTNTs) were prepared by alkali treatment of anatase titania. They were then ion-exchanged with alkali and alkaline earth metal ions to get ATNTs (A = Li+, K+, Cs+, Mg2+, Ca2+, Sr2+ and Ba2+). Gold (1-5 wt%) was supported on these nanotubes by a deposition-precipitation method and investigated as a catalyst for the selective oxidation of benzyl alcohol with air/molecular oxygen (1 atm) under solvent-and alkali-free conditions. Detailed characterization by X-ray powder diffraction, high resolution transmission electron microscopy, N-2-physisorption, diffuse reflectance UV-visible spectroscopy, X-ray photoelectron spectroscopy and CO2-temperature-programmed desorption techniques revealed that the basicity of the catalyst influences the uptake, mean particle size, electronic properties and oxidation activity of the supported gold. Benzaldehyde formed with a selectivity of about 99%. The catalytic activity (turnover frequency) was found to have a direct relationship with the basicity and an inverse relationship with the Au particle size. Among the catalysts investigated, Au/BaTNTs, having higher basicity, smaller Au particles and higher metal dispersion, showed enhanced catalytic activity than the other Au/ATNT catalysts. Pd addition to Au leading to Au-Pd/BaTNTs increased the activity (TOF) but lowered the selectivity for benzaldehyde (80 wt%). Titanate nanotubes donate electron density to Au particles, yielding electron rich Au ions, which are responsible for activating molecular oxygen and oxidizing benzyl alcohol. Au/BaTNTs, having higher basicity and lower size Au nanoparticles than the other Au/ATNT, activates molecular oxygen more easily and thereby enhances the catalytic activity.

Effects of thermal treatment of ZnO-ZnCr2O4 catalyst on the particle size and product selectivity in dehydrocyclization of crude glycerol and ethylenediamine - Sarkari, Reema; Krishna, Vankudoth; Sudhakar, Medak; Rao, Tumula Venkateshwar; Padmasri, Aytam Hari; Srinivas, Darbha; Venugopal, Akula (Kinetics and Catalysis, 2016)
The ZnO-ZnCr2O4 (Zn-Cr-O) sample obtained by decomposition of Zn-Cr hydrotalcite precursor was subjected to the thermal treatment at different temperatures and the physico-chemical properties of the Zn-Cr-O system were compared with its catalytic behavior in dehydrocyclization of crude glycerol and ethylenediamine (EDA). Upon high temperature treatment of Zn-Cr-O the Cr6+ ions underwent autoreduction to form stable Cr3+ species and the particle size of both ZnO and ZnCr2O4 increased dramatically. Thermal effect did not influence the intermolecular cyclisation of EDA to form pyrazine. By contrast, an inversely proportional dependence was found between the rate of formation of 2-methylpyrazine and the particle size of Zn-Cr-O whereas the rate of 2-pyrazinylmethanol was directly proportional to the particle size.